2014
DOI: 10.1016/j.vetmic.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bovine herpesvirus 2 and bovine herpesvirus 4 DNA in trigeminal ganglia of naturally infected cattle by polymerase chain reaction

Abstract: Establishment of latent infection within specific tissues in the host is a common biological feature of the herpesviruses. In the case of bovine herpesvirus 2 (BoHV-2), latency is established in neuronal tissues, while bovine herpesvirus 4 (BoHV-4) and ovine herpesvirus 2 (OvHV-2) latent virus targets on cells of the monocytic lineage. This study was conducted in quest of BoHV-2, BoHV-4 and OvHV-2 DNA in two hundred trigeminal ganglia (TG) specimens, derived from one hundred clinically healthy cattle, majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
11
0
6
Order By: Relevance
“…While these results differ from other experimental inoculations of cattle (Egyed et al 1996, Boerner et al 1999, they are consistent with other previously published reports (Asano et al 2003, Costa et al 2011, Campos et al 2014. Moreover, the detection of the viral genome in spleen agrees with the finding of Lopez et al (1996), regarding the ability of BoHV-4 to produce a persistent infection in a particular zone of this organ in cattle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While these results differ from other experimental inoculations of cattle (Egyed et al 1996, Boerner et al 1999, they are consistent with other previously published reports (Asano et al 2003, Costa et al 2011, Campos et al 2014. Moreover, the detection of the viral genome in spleen agrees with the finding of Lopez et al (1996), regarding the ability of BoHV-4 to produce a persistent infection in a particular zone of this organ in cattle.…”
Section: Discussionsupporting
confidence: 90%
“…shown that BoHV-4 shows an irregular pattern of dissemination in bovine tissues (Naeem et al 1991, Egyed et al 1996, Asano et al 2003, Fábián et al 2005, Campos et al 2014. It has also been reported that there are genomic variations among BoHV-4 isolates from different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of BoHV-4 has been demonstrated in many tissues, one site of persistence in both natural and experimental hosts is the cells of the macrophage/monocyte lineage (31, 32). Other potential sites of viral persistency are the trigeminal ganglia (TG), because it was shown that BoHV-4 DNA was present in the TG of naturally infected cattle, similar to the BoHV-2, which usually establish latency in neuronal tissues (33). Virus reactivation is possible following dexamethasone treatment and stress factors and, frequently, virus reactivation occurs in the absence of clinical disease (32).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha identificado el ADN viral también en el epitelio de placentas bovinas y tejidos de fetos abortados, en linfocitos y monocitos esplénicos, en células del epitelio tubular renal y en células hepáticas, en hígado, tráquea y epitelio nasal, así como en linfonódulos mesentéricos, tonsilas, timo, riñones y linfocitos de sangre periférica en bovinos que no presentaban signos clínicos de infección por BoHV-4 1, 18,19,41 . También se ha detectado en tejidos del sistema nervioso central y ganglio trigémino de bovinos con infección natural 14,16 .…”
Section: Infección Y Tropismo Viralunclassified